Cash Flow Valuation in Real Estate Development Projects with Decision Tree Analysis - Basdogan, Serhat; Onel, Hakki (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2013)
With the rapid development of real estate markets under globalization and competitive market conditions, risk evaluation has been one of the most important tasks in the process of real estate investment valuation. This paper describes the relationship between construction permit uncertainties and real estate development projects using decision tree analysis (DTA). The expected value (EV) criterion for a proposed office development project is incorporated into a conventional discounted cash flow (DCF) analysis determined by DTA. This will help utility function to come closer to the real world, so that decision making and risk analysis can be done based on more realistic data, providing better information for investors. The results are consistent with the results calculated by conventional DCF analysis. However, research demonstrates that the application of DTA obviates the deficiencies of conventional DCF analysis regarding construction permit delays and scheduling uncertainties. Results also emphasize the importance of applying EV and DTA, as construction permit delays generate a significant change in NPV of real estate development projects.
Keywords: Architecture